Naswar (Smokeless Tobacco) Use and the Risk of Oral Cancer in Pakistan: A Systematic Review With Meta-Analysis. Issue 1 (25th December 2017) - Khan, Zohaib; Suliankatchi, Rizwan Abdulkader; Heise, Thomas L; Dreger, Steffen
Abstract: Introduction: With an annual increase of 16000 new cases each year, oral cancer is the second most common cancer in Pakistan. There is conflicting evidence regarding the carcinogenicity of different forms of smokeless tobacco (SLT) from different countries. This difference in evidence may be attributed to the varied composition of SLT products used around the world, necessitating the establishment of individual risks related to each SLT product. Methods: An electronic search in relevant databases yielded 119 publications, out of which six were included in this review. Effect estimates (odds ratios (ORs)) were abstracted or calculated from the given data. A fixed effects meta-analysis was performed to assess the risk of oral cancer with the use of Naswar. Population attributable fractions (PAF) were also calculated. Results: The Meta Odds Ratio (mOR) for oral cancer associated with the "ever use" of Naswar compared to "never use" was 11.8 (95% CI = 8.4–16.4), I 2 = 67%. The pooled estimate for oral cancer in "Ever-users" of Naswar compared to "Never-users, " in the Khyber Pakhtunkhwa province was 18.3 (95% CI = 8.7–38.5), I 2 = 0%. The PAF for oral cancer associated with the use of Naswar in Pakistan was 44% (95% CI = 35–53). Discussion: This review highlights a strong relationship between oral cancer incidence and the use of Naswar in Pakistan and adds to the evidence base on the carcinogenicity of SLT products in humans. Although the synthesized evidence may not be of a high quality, it represents the "best available evidence" which can be used to inform policy. Implications: The carcinogenicity of Naswar, a form of smokeless tobacco used extensively in Pakistan, Afghanistan, and Central Asia, has yet to be recognized by the International Agency for Research on Cancer (IARC), partly due to the lack of evidence on the association of Naswar use and cancer. Additionally, Naswar is yet un-regulated in Pakistan and evades the tax net, resulting in it being freely available to both adults and children at very cheap prices compared to cigarettes, which has been the main focus of tobacco control in Pakistan. This review provides ample evidence for the IARC to declare Naswar as carcinogenic, as well as the Government of Pakistan to regulate the production and sale of Naswar .